Decisive Criteria Between Stapedotomy and Cochlear Implantation in Patients with Far Advanced Otosclerosis. Issue 3 (March 2015) - Kabbara, Bilal; Gauche, Clement; Calmels, Marie-Noelle; Lepage, Benoit; Escude, Bernard; Deguine, Olivier; Fraysse, Bernard; Marx, Mathieu
Abstract : Objectives: To describe the hearing outcomes in patients with far-advanced otosclerosis and to identify the best initial approach based on preoperative word recognition scores (WRS), pure tone averages (PTA), and radiological classification. Study Design: Retrospective case review. Setting: Academic neurotology tertiary referral center. Patients: All patients (n = 58) with preoperative air conduction PTA less than 85dB (HL), disyllabic WRS less than or equal to 50% at 60 dB (HL) with well-fitted hearing aids, and evidence of otosclerosis on CT scan, treated in our department over the past 20 years. Interventions: Stapedotomy, cochlear implantation, or both. Main Outcome Measures: Postoperative WRS after a minimum of 12 months' follow-up, percentage of patients with WRS greater than 50%. Reliability of air and bone conduction PTAs and WRS in predicting failure of stapedotomy. Results: Fifty-eight patients were divided into three groups: group I, primary stapedotomy (n = 32); group II, primary cochlear implantation (n = 9); and group III, secondary cochlear implantation (with a previous history of stapedotomy) (n = 25). The mean postoperative WRS were 50.6% (±34), 75% (±17), and 72% (±20), respectively. Sixty percent of patients in the stapedotomy group had a postoperative WRS greater than 50% requiring no further treatment, compared to 85% for cochlear implant recipients. No specific predictive factors for stapedotomy outcome could be identified. Surgical difficulties during cochlear implantation were significantly higher in patients with advanced radiological stage. Conclusion: Although cochlear implantation gives better overall results, stapedotomy with hearing aids can still be very effective in the management of patients with far-advanced otosclerosis. It should therefore be proposed as a first-line treatment.